Metabolomic Profiling of Oral Potentially Malignant Disorders and Its Clinical Values - Nur Fatinazwa Mohd Faizal; Vui King Vincent-Chong; Anand Ramanathan; Ian C. Paterson; Lee Peng Karen-Ng; Zuraiza Mohamad Zaini (Biomedicines)
Oral potentially malignant disorders (OPMD) are a group of lesions carrying the risk of developing into cancer. The gold standard to predict which lesions are more likely to undergo malignant transformation is the presence of dysplasia histologically. However, not all dysplastic lesions progress, and non-dysplastic lesions may also undergo malignant transformation. Oral carcinogenesis is a complex molecular process that involves somatic alterations and the deregulation of transcriptions, protein expression, and metabolite levels. Metabolomics, which is the scientific study of metabolites, has emerged as a promising high-throughput approach to investigate the metabolic changes of small molecules in biological pathways. In this review, we summarize the data relating to the metabolomic profiling of OPMDs, which will help elucidate the complex process of oral carcinogenesis. Furthermore, we identify that among all metabolites, citrate, pyruvate, and glutamate may serve as potential biomarkers for oral leukoplakia (OLK). Notably, metformin and gluconate have been shown to target glutamate and citrate, respectively, in cancer cells. Based on these findings, we propose that targeting these metabolites in patients with OPMD could be a promising therapeutic strategy to mitigate OPMD progression and potentially reduce the risk of malignant transformation. We also discuss the limitations and future directions of metabolomics in OPMD. Understanding these important metabolites is crucial for early detection and monitoring of oral cancer progression.